In vitro Rhizogenesis of Pineapple (Ananas comosus L.) Ì Smooth Cayenne Ì Cultivar - Almobasher, Hala Almobasher Abdollah (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
This study aimed to develop a rhiyzogenesis protocol for the in vitromicropropagated pineapple plants and subsequently acclimatization the rooted shoots. Two auxins type with different concentrations were tested and several modifications were conducted to MS medium components. Significant differences were detected among auxins tested; 0.5 mg/l IBA was the optimal concentration for root number, followed by 0.1 mg/l NAA; MS free hormones achieved the best result of root length, followed by 0.1 mg/l NAA and 0.5 mg/l IBA respectively. Increase auxins concentration up to 2.0 mg/l inhibited root length. MS medium supplemented with 20.0 g/l sucrose was the optimal concentration for both root number and length with high significant differences among other sucrose levels tested, low sucrose concentrations inhibited root formation. Decreasing MS salts concentration gave the best results of root growth parameters; whereas MS medium free salts achieved the best result for root number, followed by quarter and half MS salts strength respectively; root formation was inhibited under high salts concentration. The rooted shoots were successfully acclimatized in different types of soil; the rooted shoots were transferred to plastic pots containing: clay, sand and a mixture of clay and sand with a ratio of (1:1). The highest percentage of survival shoots were obtained in sand (91%). The pineapple plants were established successfully under greenhouse condition.